Learning through life. Reflexions about the pandemic. The peruvian experience in non formal education - Llanos Zuloaga, Martha (2021)
This essay intends to highlight the perspectives of Lifelong Learning, together with the contributions of Non-formal, Popular and Community Education. It is based on the analysis of Education and Learning in this global pandemic, which has affected the performance of the Education, Health, Employment, and Transport sectors, creating an environment of insecurity and uncertainty in the family, school, and work and community groups. Education was delivered through distance programs, virtual with digital technology for more than a year and the conclusion is that new paradigms must be introduced. Curricular homogeneity and an economic vision of education are questioned, leading to reflections on the educational agents, as well as the roles and interactions between school, family and community. Learning is only at the school level or there are other possibilities, as has been seen in communities where the digital divide is very wide. Meaningful examples are provided of Non-formal Education and Action-Reflection-Action methodologies that lead to a development of critical thinking, where adult education and early years education converge with testimonies of coordinating teachers, specialists, educators and promoters whose life stories have been followed for nearly four decades. These experiences and lessons learned constitute important proposals when facing the current emergency in the education field.